ANALISIS RASIO LIKUIDITAS UNTUK MEMPREDIKSI FINANCIAL DISTRESS PERUSAHAAN SUB SEKTOR TRANSPORTASI LAUT - Putri Ayu Anggraini; R.A. Norromadani Yuniati; Arfiana Dewi (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
The decline in the number of passengers and the volume of goods being loaded and unloaded using sea transport has resulted in a decrease in the revenue of companies in the sea freight transport subsector in Indonesia. From 2016-2022, 68% of companies in the sea transportation subsector in Indonesia had negative profits. The negative profit indicates that the company is experiencing financial difficulties that result in financial distress (FD). This study aims to see the FD condition and compare whether liquidity ratio affect financial distress conditions in the sea transportation sub sector listed on the Indonesia Stock Exchange period 2016-2022. The sample was determined using the purposive sampling technique with simple linear regression as the analysis test. The study result showed that 17,5% of companies in Indonesia experienced FD and liquidity did not affect the FD of companies in Indonesia period 2016-2022 because liquidity represented by current ratio, only measures the company’s short-term capabilities.